De leidende mens. 2 persoonlijke benadering - Luyckx, H.; Dellaert, René.; Raveschot, J.; Vander Kerken, Libert André (Leuven Acco, 1980)
Over zelfstandigheid, liefde, verantwoordelijkheid en geluk.
Keywords: #GOSA:V.Alg.M